By targeting apoptosis facilitator BCL2L13, microRNA miR-484 alleviates cerebral ischemia/reperfusion injury-induced neuronal apoptosis in mice. Issue 1 (1st January 2021) - Liu, Xindong; Wang, Xin; Zhang, Lijuan; Zhou, Yi; Yang, Le; Yang, Minghao
ABSTRACT: Neuronal apoptosis was considered as one of the main factors of cerebral ischemia/reperfusion injury. Understanding the molecular regulatory mechanism of neuronal apoptosis under the cerebral ischemia/reperfusion injury may provide the novel therapeutic targets for cerebral ischemia/reperfusion injury. However, the molecular regulatory mechanism of neurons fate determination under the cerebral ischemia/reperfusion injury remains poorly understood. This study was aimed to delve into the related molecular mechanism of miR-484 on the regulation of cerebral ischemia/reperfusion injury-induced neuronal apoptosis in mice. In this study, quantitative real-time polymerase chain reaction assays revealed that the expression level of miR-484 was down-regulated in neurons following OGD. Then, CCK8 assay western blot assay, and flow cytometry assay verified that upregulation of miR-484 increased viability and inhibited apoptosis of neurons following OGD. Further bioinformatics methods and dual-luciferase reporter assay were applied together to anticipate and certify the interaction between miR-484 and BCL2L13. Finally, cerebral infarct size assessment and TUNEL staining confirmed that overexpression of miR-484 alleviated cerebral ischemia/reperfusion injury in mice, and overexpression of BCL2L13 could abolish the effect of miR-484-suppressed cell apoptosis. All these results suggested that miR-484 alleviates cerebral ischemia/reperfusion injury-induced neuronal apoptosis in mice by targeting apoptosis facilitator BCL2L13. Graphical Abstract: uf0001